3(x-2)=9(9x+2)

Simple and best practice solution for 3(x-2)=9(9x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)=9(9x+2) equation:


Simplifying
3(x + -2) = 9(9x + 2)

Reorder the terms:
3(-2 + x) = 9(9x + 2)
(-2 * 3 + x * 3) = 9(9x + 2)
(-6 + 3x) = 9(9x + 2)

Reorder the terms:
-6 + 3x = 9(2 + 9x)
-6 + 3x = (2 * 9 + 9x * 9)
-6 + 3x = (18 + 81x)

Solving
-6 + 3x = 18 + 81x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-81x' to each side of the equation.
-6 + 3x + -81x = 18 + 81x + -81x

Combine like terms: 3x + -81x = -78x
-6 + -78x = 18 + 81x + -81x

Combine like terms: 81x + -81x = 0
-6 + -78x = 18 + 0
-6 + -78x = 18

Add '6' to each side of the equation.
-6 + 6 + -78x = 18 + 6

Combine like terms: -6 + 6 = 0
0 + -78x = 18 + 6
-78x = 18 + 6

Combine like terms: 18 + 6 = 24
-78x = 24

Divide each side by '-78'.
x = -0.3076923077

Simplifying
x = -0.3076923077

See similar equations:

| (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y | | 1000x+50=30 | | -1+m=m-8 | | -27y=-108 | | -6x^2+3=-15 | | 4y+2=180 | | -6f+1=13 | | 3x+60=10x+11 | | 23=-7(6v+7)+5(1-5v) | | 1.9/250=x/650 | | y-18=21 | | 4(2r+12)=6(4r-32) | | -5n+12=7n | | x^4+x^3-19x^2+x-20=0 | | -16x^2+80x+20=20 |

Equations solver categories